Journal of the American Oriental Society - American Oriental Society (New Haven [etc.] American Oriental Societ)
"Proceedings" or "Select minutes of meetings" are included in each volume (except v. 3, 12). List of members in each volume.
SERBIB/SERLOC merged record
Keywords: American Oriental Society; Oriental philology